Stress Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan - Timotius Juniko Kriskito; Hesty Prima Rini (IPM2KPE, 2022)
This study aims to determine the effect of job stress and job satisfaction on the performance of IndiHome Sales employees at PT. Telkom Indonesia Witel North Surabaya. This research method is quantitative. The population in this research is 253 IndiHome Sales Employees of PT. Telkom Indonesia Witel North Surabaya. The sampling method used purposive sampling technique, with a sample of 72 people calculated using the slovin formula. Data analysis using Partial Least Square (PLS). The results showed, a) the variable of work stress on employee performance variables has a path coefficients value of -0.273524, and a T-statistic value of -3.884768 > 1.96 (from table value Zα = 0.05) or P- Value 0.000 <0.05, then the result is significant (negative); b) the job satisfaction variable on employee performance variables has a path coefficients value of 0.705283, and a T-statistic value of 10.094021 > 1.96 (from the table value Zα = 0.05) or P-Value 0.000 <0.05 , then the result is significant (positive); c) the value of R2 (R square) in this study was 0.9408 or 94.09%, meaning that the influence of the independent variable was 94.09% while the remaining 5.91% was influenced by other factors. In conclusion, work stress affects employee performance, and job satisfaction affects employee performance. Keywords: Job Satisfaction, Employee Performance, Work Stress